Clinical case of papulo-pustular rosacea - Anna L. Evseeva; Vera V. Ryabova; Sergei V. Koshkin (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
The article presents a clinical case of papulopustular rosacea from our own practice. First of all, the patient's anamnesis is extremely interesting: family history (his brother has episodes of reddening of the face), the onset of rosacea against the background of a stressful situation, the presence of gastric diseases, the connection with nutritional factors. One of the first mentions of rosacea belongs to Avicenna, who in his writings described the clinical picture of rhinophyma ("badschenan", later renamed "abedsamen"). The pineal nose, dotted with "serpentine" vessels, has traditionally been associated with excessive drinking. Currently, the role of alcohol as an etiological factor is not paramount, but its aggravating effect has been proven. Despite the typical picture of rosacea, our patient has been receiving therapy for seborrheic dermatitis and other diseases several times over the course of several years. Probably, the specialists had doubts about the possible diagnosis of rosacea in a male patient under the age of 30.